A Comparison of the Subjective Responses to Two Hypofractionated Palliative Radiotherapy Regimens in Patients with Locally Advanced Inoperable Head and Neck Cancer - Sonar, Mongal; Bhattacharyya, Mouchumee; Singh, Moirangthem Nara; Yanthan, Yanpothung; Neog, Moniprom; Das, Ankita; Das, Abhinandan; Das, Tapashi; Sharma, Prashasti (Asian Pacific Journal of Cancer Care, 2023)
Background: Patients with advanced head and neck cancers typically succumb to uncontrolled local disease. Even with aggressive therapy, median survival is about 12 months, and the five-year overall survival <20%. Radiation treatment used in palliative setting is an option for some patients who are not eligible for curative therapy. Palliative treatment aims to reduce cancer-related symptoms while causing the fewest side effects and toxicities as possible. Materials and Methods: After approval from the institutional ethical committee, a prospective randomised study was conducted on squamous cell carcinomas of locally advanced head and neck cancer patients treated with palliative radiotherapy. A total of 62 patients were chosen and randomly assigned (1:1) to one of two treatment groups. Patients in Arm-A received 40 Gy in 16 fractions of radiation therapy, while those in Arm-B received 30 Gy in 10 fractions. The primary goal was to evaluate the subjective responses in both arms, including pain, dysphagia, and bleeding. Results: Mean pain score after completion of radiotherapy was 4.69 and 3.65 in Arm-A and Arm-B respectively, with significant p-value of <0.001. The mean pain score 3 months after completion of treatment was 2.39 and 3.61 in Arm-A and Arm-B respectively, with significant p-value of <0.001. Comparing both the arms dysphagia relief at completion of treatment was higher in Arm-B compared to Arm- A with mean scores of 1.95 and 2.03 which was not significant. After 3 months, it was higher in Arm-A compared to Arm-B, which was also insignificant, while Arm A patients received significant relieve from dysphagia at completion of treatment and during follow-ups. Bleeding was not a significant factor in both the arms. Conclusion: Our study found for immediate pain relief, 30Gy/10 fractions was better, but for long-term relief, 40Gy/16 fractions was better. Alleviation of swallowing difficulties was seen in both regimens.